Does ESG Disclosure Affect Profitability? Evidence from Shariah-Compliant Firms in Indonesia and Malaysia : Does ESG Disclosure Affect Profitability? Evidence from Shariah-Compliant Firms in Indonesia and Malaysia - Desyetti; Lukman, Syukri; Rahim, Rida; Adrianto, Fajri (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2025)
Sustainability issues and the implementation of Environmental, Social, and Governance (ESG) disclosure have become a major focus in the global business environment, including among Shariah-compliant firms. Although many firms have adopted sustainability initiatives, the contribution of ESG disclosure to financial performance remains debated. This study aims to examine the effect of ESG disclosure on the profitability of Shariah-compliant firms in Indonesia and Malaysia. Leverage, earnings management, and firm size are included as control variables. The sample consists of Shariah-compliant firms listed on the Indonesia Stock Exchange and Bursa Malaysia over a specified observation period. The analysis employs multiple regression using a random effect model approach. The findings reveal that, overall, ESG disclosure negatively affects profitability in both the combined sample of Indonesia and Malaysia and the Indonesian sample individually. In contrast, among Shariah-compliant firms in Malaysia, ESG disclosure does not have a significant impact on profitability, whereas earnings management shows a positive effect. These results highlight the need to enhance the substance of sustainability disclosures to better support financial value creation. This study contributes to the extension of agency theory and signaling theory within the context of Shariah-compliant businesses and opens avenues for future research on strengthening governance practices based on Islamic ethical values.